Combined evaluation of sexually transmitted infections in HIV-infected pregnant women and infant HIV transmission. - Kristina Adachi; Jiahong Xu; Nava Yeganeh; Margaret Camarca; Mariza G Morgado; D Heather Watts; Lynne M Mofenson; Valdilea G Veloso; Jose Henrique Pilotto; Esau Joao; Glenda Gray; Gerhard Theron; et al. (PLoS ONE, 2018)
BACKGROUND:Sexually transmitted infections (STIs) including Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG), Treponema pallidum (TP), and cytomegalovirus (CMV) may lead to adverse pregnancy and infant outcomes. The role of combined maternal STIs in HIV mother-to-child transmission (MTCT) was evaluated in mother-infant pairs from NICHD HPTN 040. METHODOLOGY:Urine samples from HIV-infected pregnant women during labor were tested by polymerase chain reaction (PCR) for CT, NG, and CMV. Infant HIV infection was determined by serial HIV DNA PCR testing. Maternal syphilis was tested by VDRL and confirmatory treponemal antibodies. RESULTS:A total of 899 mother-infant pairs were evaluated. Over 30% had at least one of the following infections (TP, CT, NG, and/or CMV) detected at the time of delivery. High rates of TP (8.7%), CT (17.8%), NG (4%), and CMV (6.3%) were observed. HIV MTCT was 9.1% (n = 82 infants). HIV MTCT was 12.5%, 10.3%, 11.1%, and 26.3% among infants born to women with CT, TP, NG or CMV respectively. Forty-two percent of HIV-infected infants were born to women with at least one of these 4 infections. Women with these infections were nearly twice as likely to have an HIV-infected infant (aOR 1.9, 95% CI 1.1-3.0), particularly those with 2 STIs (aOR 3.4, 95% CI 1.5-7.7). Individually, maternal CMV (aOR 4.4 1.5-13.0) and infant congenital CMV (OR 4.1, 95% CI 2.2-7.8) but not other STIs (TP, CT, or NG) were associated with an increased risk of HIV MTCT. CONCLUSION:HIV-infected pregnant women identified during labor are at high risk for STIs. Co-infection with STIs including CMV nearly doubles HIV MTCT risk. CMV infection appears to confer the largest risk of HIV MTCT. TRIAL REGISTRATION:NCT00099359.